2019
DOI: 10.1177/0192623319843052
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence of Neurogenesis in Adult Rat Sympathetic Ganglia Following Guanethidine-Induced Neuronal Loss

Abstract: The potential for neurogenesis in the cranial (superior) cervical ganglia (SCG) of the sympathetic nervous system was evaluated. Eleven consecutive daily doses of guanethidine (100 mg/kg/d) were administered intraperitoneally to rats in order to destroy postganglionic sympathetic neurons in SCG. Following the last dose, animals were allowed to recover 1, 3, or 6 months. Right and left SCG from guanethidine-treated and age-matched, vehicle-treated control rats were harvested for histopathologic, morphometric, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…On one hand, Melo et al reported an age-related increase in the SCG volume and the total number of SCG neurons [49], and Ladd et al along with the increasing SCG volume, showed the presence of new-born neurons in old animals by using BrdU technique [50]. On the other hand, Walters et al recently showed that there is no evidence of active neurogenesis in sympathetic ganglia [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On one hand, Melo et al reported an age-related increase in the SCG volume and the total number of SCG neurons [49], and Ladd et al along with the increasing SCG volume, showed the presence of new-born neurons in old animals by using BrdU technique [50]. On the other hand, Walters et al recently showed that there is no evidence of active neurogenesis in sympathetic ganglia [51].…”
Section: Discussionmentioning
confidence: 99%
“…3 b and 4 g, the larger number of neurons and a smaller number of TUNEL-positive cells in sleep-deprived rats receiving curcumin in comparison with the CSD groups, confirming curcumin in preventing cell death, which is in line with previous studies [ 30 , 47 ]. The previous studies show that curcumin increases cell survival [ 58 ] and based on a recently published study, a lack of proliferation activity has been reported in the SCG [ 51 ]. Besides, by inhibiting pro-apoptotic factors such as Bcl-2-associated X protein [ 59 ] and activating silent information regulator 1 (SIRT1) [ 60 ] curcumin has antioxidant properties.…”
Section: Discussionmentioning
confidence: 99%
“…Kaliyaperumal et al 70 review the biology of pain, available rodent pain models, and discussed the important role of pathologists in interpreting data and validating these models. This section concludes with a series of case reports exploring common iatrogenic PNS lesions associated with experimental manipulation rather than test article administration ( Bangari et al ); 71 unusual manifestations of autonomic neuropathy ( Walters et al ), 72 which historically is a vastly unappreciated aspect of PNS neurotoxicity; and common PNS background findings ( Butt et al 73 and Weber et al 74 ) that should not be assigned as test article-related lesions.…”
mentioning
confidence: 99%